The Contribution of Hepatic Macrophage Heterogeneity during Liver Regeneration after Partial Hepatectomy in Mice - Pengfei Ma; Wenchao Zhao; Chunchen Gao; Zhiwei Liang; Longshuan Zhao; Hongyan Qin; Xiaolin Sun (Journal of Immunology Research)
Background and Aim. Hepatic macrophage is a heterogenetic population in origin and function. It is known to participate in the coordination of all phases of liver regeneration after partial hepatectomy (PHx). However, as yet, there is no research focused on the dynamics of macrophage subsets of different origins and functions after PHx. Methods. In the present study, we investigated hepatic macrophage heterogeneity in murine liver regeneration after 2/3 PHx through immunofluorescence staining, fluorescence-activated cell sorting analysis, and quantitative reverse transcription-polymerase chain reaction. Results. Our research showed that Kupffer cells reduced rapidly in the early PHx and restored gradually depending on local proliferation and replenishment from infiltrating monocyte-derived macrophages. The ratio of ly6Chi to ly6Clo subset of macrophages in the liver changed dynamically, and hepatic macrophage function exhibits a significant difference in different stages of liver regeneration. Moreover, blocking infiltrating monocyte-derived macrophage recruitment augmented Kupffer cell proliferation but impaired the restoration of the hepatic macrophage pool, which led to delayed hepatocyte mitosis and liver regeneration. Conclusions. Our data suggest that hepatic macrophage changes dynamically in origin and function during liver regeneration following PHx and macrophage-targeted liver regeneration should consider macrophage heterogeneity.